PENYUTRADARAAN FILM FIKSI KATRESNAN DENGAN PENEKANAN EKSPRESI UNTUK MEMPRESENTASIKAN EMOSI HAYATRI - Khairun Nisah (Cinelook: Journal of Film, Television, and New Media, 2025)
Apart from the blessing of parents, there are some restrictions that couples who are about to get married should not do. One of them is the ban on marriage, namely from the Javanese community the prohibition on the marriage of the first child with the first child. The film Katresnan tells the story of the main character who experiences many problems in his life after getting married. Hayatri is a child of Hastomo, a person who is guided by primbon books which contain customs and habits that exist in Javanese society. Hayatri's expressions are emphasized in the direction of the fiction film Katresnan which aims to present Hayatri's emotions. The object of the creation of the film Katresnan is a scenario that tells of a girl named Hayatri who wants to marry a man of her choice, but her father doesn't approve because there are several things that become problems in the primbon book. Likewise, after getting married, Hayatri wanted to move house, but her father didn't approve because the house didn't suit their weton either.The aesthetic concept for the creation of the Katresnan film is in the emphasis on expression, presenting Hayatri's emotions by depicting facial expressions, voice, attitudes and gestures. The Katresnan film is embodied in a 23-minute film with a rich family drama genre with expressions to add to the attractiveness of the scene. Key words: Fiction film, directing, expression, emotion